The Role of Islamic Religious Education Teachers in Instilling an Understanding of Religious Moderation in 10th Grade Students at Al-Qur’an Tri Bhakti At-Taqwa High School - Hanifurrohman, Hanifurrohman; Muslimin, Ahmad; Jaenullah, Jaenullah (International Journal on Advanced Science, Education, and Religion, 2025)
This study aims to examine how Islamic Religious Education (PAI) instructors support the development of religious moderation awareness among 10th-grade students at Al-Qur'an Tri Bhakti At-Taqwa Senior High School. The study is motivated by increasing issues of intolerance and exclusive religious views among students, which highlight the strategic role of educators in internalizing the values of moderation. Using a descriptive qualitative approach, data were collected through in-depth interviews, direct observations, and documentation involving PAI teachers, the school principal, and several 10th-grade students. The findings indicate that PAI instructors play a significant role in cultivating moderate attitudes by serving as mentors, educators, and role models. Through instruction emphasizing tolerance, justice, openness, and real-life examples in social interactions, teachers help enhance students’ awareness of diversity and respect within religious communities. According to the principal, M. Fathurrahman, M.Pd., the school is committed to educating a generation with noble character and a moderate understanding of religion. Nevertheless, several challenges were identified, including diverse student backgrounds, limited instructional time for PAI, and the influence of family and community environments that often promote exclusive perspectives. Teachers addressed these challenges through personalized guidance, reflective discussions, and the integration of moderate values into religious activities and cross-disciplinary learning. Interviews with students revealed positive changes in their attitudes and behaviors toward religious differences.